The Analysis of Teaching English Pronunciation at Young Learners - Astina; Nurhamdah; Amzah (Institut Agama Islam Negeri Parepare, 2020)
The aim of this study is to describe the technique that teacher use in teaching English pronunciation to young learners and the difficulties in teaching pronunciation for young learners at SD Negeri 82 Parepare. The sample of this study is the teacher and students at 5th Grade of SD Negeri 82 Parepare. The research method used in this study is a descriptive qualitative research. The instruments used in this study are observation checklist, list of questions, and document. First, observation is done in order to choose participants and to look the activity in the class, whereas interview is conducted in order to have other information, and document conducted to support data of this research. From the result of data analysis, it is found that the teacher used two techniques in teaching English pronunciation; drill and visual aids techniques. In drill technique the teacher used repetition drill, whereas in visual aids teacher use a picture. Those techniques still effective for young learners. However, this study gives suggestion to all teachers who teach pronunciation as reference and researchers to investigate the same research about teaching pronunciation. From the observation and interview with the teacher and some student, it found that there are some difficulties in teaching and learning pronounciation. It is luck of media to use in teaching process, the influence of student’s mother tongue, and uninterested student in learn English.